Determinants of job satisfaction levels among community development officers in Oyo State, Nigeria (2019)
The objective of this study was to examine empirically the determinants of job satisfaction levels among community development officer in Oyo State, Nigeria. Due to this, two research questions were formulated and answered. All community development officers across thirty-three local government areas of Oyo state formed the target population. However, fifteen local governments were chosen for the study from the existing number, also, simple random sampling technique which was stratified in nature and operation was used to select seven-hundred and seventy one (771) respondents which cut across three strata (that is three senatorial districts). Structured questionnaire was used to elicit information from the respondents, while descriptive component of statistics was employed to analyse the data generated from the instrument. The empirical findings from demographic attributes of the respondents revealed that the majority of the community development officers participated in the study were female by gender, first degree or Higher National Diploma by qualifications, spent between 4-6 years in service as community development agent, Christian by religious affiliation, and inspector in terms of cadre. Based on the determinants levels of job satisfaction, it was discovered from majority point of view that the current placement in the job, future prospect of the career, availability and accessibility of on-the-job training, favourable working conditions, regular promotion, routine of the job, level of motivation, monthly remuneration among others were some of the determinants of job satisfaction levels among community development officers. The study recommended constant and regular initiation of programmes like on-the-job training, regular payment of wages and salaries, attractive social welfare packages to mention a few for the community development officers regardless of their gender and religious affiliation